The role of the CD8+ T cell compartment in ageing and neurodegenerative disorders - Terrabuio, Eleonora; Zenaro, Elena; Constantin, Gabriela (Frontiers in Immunology, 2023)
CD8+ lymphocytes are adaptive immunity cells with the particular function to directly kill the target cell following antigen recognition in the context of MHC class I. In addition, CD8+ T cells may release pro-inflammatory cytokines, such as tumor necrosis factor-a (TNF-a) and interferon-g (IFNg), and a plethora of other cytokines and chemoattractants modulating immune and inflammatory responses. A role for CD8+ T cells has been suggested in aging and several diseases of the central nervous system (CNS), including Alzheimer's disease, Parkinson's disease, multiple sclerosis, amyotrophic lateral sclerosis, limbic encephalitis-induced temporal lobe epilepsy and Susac syndrome. Here we discuss the phenotypic and functional alterations of CD8+ T cell compartment during these conditions, highlighting similarities and differences between CNS disorders.Particularly, we describe the pathological changes in CD8+ T cell memory phenotypes emphasizing the role of senescence and exhaustion in promoting neuroinflammation and neurodegeneration. We also discuss the relevance of trafficking molecules such as selectins, mucins and integrins controlling the extravasation of CD8+ T cells into the CNS and promoting disease development. Finally, we discuss how CD8+ T cells may induce CNS tissue damage leading to neurodegeneration and suggest that targeting detrimental CD8+ T cells functions may have therapeutic effect in CNS disorders.